Role of nucleosome remodeling in neurodevelopmental and intellectual disability disorders - López, Alberto J.; Wood, Marcelo A. (Frontiers in Behavioral Neuroscience, 2015)
It is becoming increasingly important to understand how epigenetic mechanisms control gene expression during neurodevelopment. Two epigenetic mechanisms that have received considerable attention are DNA methylation and histone acetylation. Human exome sequencing and genome-wide association studies have linked several neurobiological disorders to genes whose products actively regulate DNA methylation and histone acetylation. More recently, a third major epigenetic mechanism, nucleosome remodeling, has been implicated in human developmental and intellectual disability disorders. Nucleosome remodeling is driven primarily through nucleosome remodeling complexes with specialized ATP-dependent enzymes. These enzymes directly interact with DNA or chromatin structure, as well as histone subunits, to restructure the shape and organization of nucleosome positioning to ultimately regulate gene expression. Of particular interest is the neuron-specific Brg1/hBrm Associated Factor (nBAF) complex. Mutations in nBAF subunit genes have so far been linked to Coffin-Siris syndrome, Nicolaides-Baraitser syndrome, schizophrenia, and Autism Spectrum Disorder. Together, these human developmental and intellectual disability disorders are powerful examples of the impact of epigenetic modulation on gene expression. This review focuses on the new and emerging role of nucleosome remodeling in neurodevelopmental and intellectual disability disorders and whether nucleosome remodeling affects gene expression required for cognition independently of its role in regulating gene expression required for development.